The usefulness of B-cell lymphoma-2 immunohistochemical stain in the differentiation between reactive atypia and dysplasia/carcinoma in the gallbladder - Alkhamiss, Abdullah Saleh (International Journal of Health Sciences, 2024)
Objective: The differentiation between reactive atypical changes and dysplasia/carcinoma in the daily cases of cholecystectomies is a routine histopathological challenge. Up to our knowledge, no immunohistochemical marker can defiantly differentiate between these two changes. Many promising markers have been proposed to be helpful tools in this situation. One of them is B-cell lymphoma-2 (BCL-2) immunohistochemical stain. Therefore, this study aims to evaluate its usefulness as a marker that might be helpful in such challenging cases. Methods: From the archive of the histopathology laboratories of Qassim University Medical City and King Fahad Specialist Hospital in Qassim, five dysplastic/neoplastic gallbladder cases were collected (in the shape of formalin-fixed, paraffin-embedded blocks) as well as five cholecystitis with reactive atypical changes cases. Two slides from each block were prepared: One was stained with H&E and the other was stained immunohistochemically with BCL-2. The slides were evaluated by two histopathologist consultants in the same sitting using multiheaded microscope to confirm the original diagnosis and to evaluate the BCL-2 staining. Results: Five dysplastic/carcinoma cases and five cholecystitis with reactive atypia were collected. The original diagnoses were confirmed by two pathologists. They also confirmed that all the BCL-2 stained slides (with the exception of one reactive case) were negative for BCL-2 immunohistochemical stain. Conclusion: BCL-2 immunohistochemical stain is not a promising marker in the differentiation between reactive epithelium and dysplasia/carcinoma in the gallbladder.